Modeling and Optimization For H2s Adsorption From Wastewater Using Coconut Shell Based Activated Carbon - Habeeb, Omar Abed; K., Ramesh; Ali, Gomaa A. M.; M. Y. M., Yunus; Thanusha, T. K.; Olalere, Olusegun Abayomi (AENSI Publishing, 2016)
In the current work, the Response Surface Method (RSM) is used to optimize the adsorption efficiency of hydrogen sulfide (H2S) onto the coconut shell activated carbon. The considered design (or operating) variables are; initial H2S concentration, adsorption contact time and adsorbent dosage, while the response variable is H2S equilibrium concentration (Ce). Coconut shell is an agricultural by-product in Malaysia, which could be used as a source of carbon. The combination of the operating variables was determined based on the 23 factorial experimental design method. On the other hand, SEM, EDX and FTIR techniques were utilized to investigate the physical and chemical properties of the prepared activated carbon. H2S removal efficiency was investigated using batch mode process. It was found that the adsorption contact time and the initial H2S concentration play a dominant role in affecting the adsorption process. Moreover, the ANOVA test showed that the model is significant. It is observed that the H2S adsorption rate can be better represented by the pseudo-first-order model as compared to the second order model. The isotherm adsorption mechanism models are also investigated in the current work. Freundlich model was found to be the well fitted adsorption process model. The study revealed that, coconut shell based activated carbon is a good candidate adsorbent for removing dissolved H2S from synthetic petrochemical refinery wastewater.